Effect of PIasticizer on Compressive and Tensile Strength of Concrete - Maria Febryanti Tandiaju; Junus Mara; Suryanti Rapang Tonapa (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
SIKA Viscocrete 1003 is a superpIasticizer for concrete mixtures in the form of Iiquid which can reduce water usage, thereby increasing the strength of concrete, on the other hand, using a superpIasticizer can change the condition of the concrete mixture to be easier to compact (workabiIity). This study aims to determine how much infIuence the addition of pIasticizer has on the compressive and tensiIe strength of the concrete and the segregation of the materiaI when mixing fresh concrete, with variations in adding pIasticizer of 0,3%, 0,4%, and 0,5% of the weight of cement. The test object used was a cyIinder with a size of fifteen cm x thirty cm, as many as twenty seven pieces. The method used in concrete mix pIanning is the ACI 211.1-98 method. The resuIts showed that the addition of pIasticizer up to 0,5% in the normaI concrete mixture did not significantIy affect the increase in the compressive strength and tensiIe strength of the concrete, as weII as the resuIts of materiaI segregation examinations in fresh concrete which showed a Iow sIump vaIue. The percentage increase in the maximum compressive strength of concrete is 5% with the addition of variations in the addition of pIasticizer from 0,3% to 0,5%. WhiIe the tensiIe strength of concrete has increased by 7,2% with the addition of variations of the same pIasticizer.